2015
DOI: 10.1007/s00590-015-1654-x
|View full text |Cite
|
Sign up to set email alerts
|

Porous tantalum in spinal surgery: an overview

Abstract: Porous tantalum is an open-cell metal structure that approximates the appearance of human cancellous bone. It has a low modulus of elasticity, close to that of subchondral and cancellous bones, leading to better load transfer and minimizing the stress-shielding phenomenon. Its coefficient of friction is one of the highest among biomaterials, allowing for sufficient primary stabilization of implants, possibly even without screw fixation. Different fusion rates have been achieved in anterior cervical fusion, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Experimental studies demonstrated that the EM of TM corresponds to a mixture of bone obtained from human subchondral and cancellous bone, 13,53 leading to better load transfer and minimizing the stress-shielding phenomenon. Also for these reasons TM cages appear highly suitable for ACF after cervical microdiskectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies demonstrated that the EM of TM corresponds to a mixture of bone obtained from human subchondral and cancellous bone, 13,53 leading to better load transfer and minimizing the stress-shielding phenomenon. Also for these reasons TM cages appear highly suitable for ACF after cervical microdiskectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Sagomonyants et al have shown that porous tantalum stimulates proliferation and osteogenesis of osteoblasts (12). Due to its unique properties, it has been successfully used in cervical and in a variety of lumbar spine procedures as a sound interbody device (13).…”
Section: Discussionmentioning
confidence: 99%
“…In hip surgery, TM implants (without using bone graft) have been shown to be no less inferior to traditional implants when managing acetabular defects and pelvic discontinuity during acetabular revision arthroplasty 21. In spine surgery, TM implants without graft have shown satisfactory fusion rates and clinical outcomes in both cervical corpectomy and lumbar interbody fusion surgery 22. In knee surgery, TM implants have shown comparable results in total knee arthroplasty when compared with cemented implants, particularly in the young and active population 23.…”
Section: Discussionmentioning
confidence: 99%